The Metabolic-Inflammatory Axis in Brain Aging and Neurodegeneration - Enrique Cadenas (Frontiers Research Topics, 2017)
Impairment of energy metabolism is a hallmark of brain aging and several neurodegenerative diseases, such as the Alzheimer's disease (AD). Age- and disease-related hypometabolism is commonly associated with oxidative stress and they are both regarded as major contributors to the decline in synaptic plasticity and cognition. Neuroinflammatory changes, entailing microglial activation and elevated expression of inflammatory cytokines, also correlate with age-related cognitive decline. It is still under debate whether the mitochondrial dysfunction-induced metabolic deficits or the microglia activation-mediated neuroinflammation is the initiator of the cognitive changes in aging and AD. Nevertheless, multiple lines of evidence support the notion that mitochondrial dysfunction and chronic inflammation exacerbate each other, and these mechanistic diversities have cellular redox dysregulation as a common denominator. This research topic focuses on the role of a metabolic-inflammatory axis encompassing the bioenergetic activity, brain inflammatory responses and their redox regulation in healthy brain aging and neurodegenerative diseases. Dynamic interactions among these systems are reviewed in terms of their causative or in-tandem occurrence and how the systemic environment, -e.g., insulin resistance, diabetes, and systemic inflammation-, impacts on brain function.